Identifikasi Motivasi Pekerja Pada Proyek Konstruksi Di Kabupaten Aceh Barat - Zakia Zakia (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2018)
Motivation aspect becomes very important to boost the spirit and performance of the workers on construction project. This performance improvement becomes an important challenge in the construction industry in Indonesia. The concept of motivation applied in a work environment will provide support to the worker. Therefore, we need a concept of motivation that can be applied in the work environment. The purpose of this study is to identify and analyze the factors that affect the performance of construction workers and recommend alternative motivation of employers to construction projects in West Aceh regency. The research is based on theoretical biotechnological yoruteorical needs of Maslow's needs. The method used in this research is descriptive analysis. The results of this research calculation using the help of computer program SPSS (Statistical Product and Service Solution) version 16.00. validity test, reliability test, and frequency test of the analysis can be seen that bonuses and additional wages are top priority on physical needs with a total value of 135, a good safety program is a top priority on security and safety needs with a total value of 130, a good relationship with fellow workers being the top priority of social needs with a total of 123 values, being able to complete the job well becomes a top priority on reward needs with a total score of 122, setting a good work schedule a top priority on the need for identity with a total value of 115, while alternatives which can be done to identify the motivation of construction workers in Kabupatan Aceh Barat is to provide bonuses and additional wages when workers can complete the work before the target as a form of appreciation.  Keywords :Workers, motivation, SPSS